2012
DOI: 10.1016/j.jvb.2011.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Career and employer change in the age of the ‘boundaryless’ career

Abstract: This study examined the direct effect of individual career concerns on career and employer change intention, as well as the buffering influence of organisational commitment on this relationship, based on the AMO model of behavioural change intention. Survey data, collected from 341 employees across industry sectors in Australia, showed that 'exploration' concerns related positively to both employer and career change intentions; the impact of exploration concerns on career change intention was buffered by affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 40 publications
4
29
0
2
Order By: Relevance
“…This finding supports the work of Bedeian et al (1991) whose concept of expected utility of one's present job was based primarily on the degree to which one's present job was relevant to one's longer term professional growth and development (Hess et al, 2012). This study results support the works of Weng and McElroy (2012), Xiong (2008) and Hess et al(2012). In Weng and McElroy"s study, dimensions of career growth were negatively related to turnover intentions and affective occupational commitment was found to partially mediate these relationships among Chinese employees.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This finding supports the work of Bedeian et al (1991) whose concept of expected utility of one's present job was based primarily on the degree to which one's present job was relevant to one's longer term professional growth and development (Hess et al, 2012). This study results support the works of Weng and McElroy (2012), Xiong (2008) and Hess et al(2012). In Weng and McElroy"s study, dimensions of career growth were negatively related to turnover intentions and affective occupational commitment was found to partially mediate these relationships among Chinese employees.…”
Section: Resultssupporting
confidence: 87%
“…In Xiong"s (2008) study, it is demonstrated that remuneration growth constitutes one reason for employees to remain with their employing organizations among Chinese employees (Weng & McElroy, 2012). Hess et al (2012) found similar results among Australian employees.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…(Hess, Jepsen, & Dries, 2012;Holmes & Cartwright, 1994;Muja & Appelbaum, 2012). There has been little mention of scientific career paths and a search of the available literature has provided scant information about scientists changing careers.…”
Section: Exploring the Factors That Affect A Successful Change From Amentioning
confidence: 99%
“…The current paper clearly demonstrates that researchers need to be more mindful of the contextual forces shaping careers. CDI 16,4 Historical, cultural, and ideological contexts impact significantly on people's subjective definitions of career success, which in turn affects their career behaviors and decisions. All three contextual factors might generate barriers and opportunities to the construction of meaning in careers (Blustein et al, 2004).…”
Section: Adopt a Dual Viewpoint Of Careermentioning
confidence: 99%